Piecemeal remarks on János Kornai’s life-work - Bernard Chavance (Revue de la Régulation, 2022)
On the occasion of Amartya Sen’s discussion of “Marx after Kornai” (Sen, 2021), the note evokes two questions in the work of János Kornai. The first is his attitude to normative assessment in conditions of conflict or tension between values, the second is his relation to Marx, with specific remarks about capitalism, inequalities and democracy.